2022
DOI: 10.3389/fphar.2022.842313
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis-Related Inflammasome Pathway: A New Therapeutic Target for Diabetic Cardiomyopathy

Abstract: Pyroptosis is a highly specific type of inflammatory programmed cell death that is mediated by Gasdermine (GSDM). It is characterized by inflammasome activation, caspase activation, and cell membrane pore formation. Diabetic cardiomyopathy (DCM) is one of the leading diabetic complications and is a critical cause of fatalities in chronic diabetic patients, it is defined as a clinical condition of abnormal myocardial structure and performance in diabetic patients without other cardiac risk factors, such as hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 126 publications
(150 reference statements)
0
24
0
Order By: Relevance
“…Enhancing antioxidant defense may protect against diabetes-induced cardiac dysfunction ( 31 ). As one of the most important transcription factors, Nrf2 exerts antioxidant and anti-apoptotic effects by activating multiple antioxidant genes, including HO-1 and NQO1 ( 6 , 32 ). Our study showed that hyperglycemia increased ROS and MDA levels in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing antioxidant defense may protect against diabetes-induced cardiac dysfunction ( 31 ). As one of the most important transcription factors, Nrf2 exerts antioxidant and anti-apoptotic effects by activating multiple antioxidant genes, including HO-1 and NQO1 ( 6 , 32 ). Our study showed that hyperglycemia increased ROS and MDA levels in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of hyperglycemia-induced myocardial injury include cardiac inflammation, increased reactive oxygen species (ROS), interstitial fibrosis, and cardiac cell apoptosis ( 2 , 5 ). Such adverse reactions induce structural remodeling and affect heart diastolic function ( 6 ). Therefore, pharmacological inhibition of inflammation, ROS, and cell apoptosis has been proven to confer cardioprotection.…”
Section: Introductionmentioning
confidence: 99%
“…Programmed cell death is a hot issue in biological and medical research, and targeting the cell death process is a common approach in tumor therapy. However, current compounds that induce programmed death are only effective against certain tumor cells, and different types of cancers seem to have different sensitivities to programmed death ( 177 179 ). Efforts to understand the sensitivity of different tissue tumors to programmed death are important for the practice of clinical application of programmed death in tumor therapy.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Pyroptosis is a type of inflammatory programmed cell death. It is mediated by gasdermin (GSDM) and is characterized by inflammasome activation, caspase activation, and formation of cell membrane pores [15][16][17]. GSDMDmediated pyroptosis has a role in the occurrence and development of diabetic cardiomyopathy and diabetic nephropathy [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is mediated by gasdermin (GSDM) and is characterized by inflammasome activation, caspase activation, and formation of cell membrane pores [15][16][17]. GSDMDmediated pyroptosis has a role in the occurrence and development of diabetic cardiomyopathy and diabetic nephropathy [15,18,19]. Although the relationship between diabetic vascular injury and pyroptosis is not well established, current studies prompted us to clarify the significance of pyroptosis in diabetic vascular injury, the initial engine in pathological progress of diabetes.…”
Section: Introductionmentioning
confidence: 99%